Analysis of Damage to Abdul Haris Nasution Road Section from STA 4+400 to STA 8+700, Batu Nadua District, Padangsidimpuan City - Simanullang, Ramot; Rafii, Ahmad; Pohan, Rizky Febriani (PT Inovasi Pratama Internasional, 2024)
Highways are one of the most important land transportation infrastructures, so good road pavement design is a must. Good road pavement is also expected to provide a sense of safety and comfort in driving, especially affect the smooth flow of traffic. One of the causes of road damage is the lack of maintenance costs which results in a decrease in the quality of implementation. The rapid growth of vehicles has an impact on traffic density, both on inner-city and outer-city roads, so that it is necessary to improve the quality and quantity of road infrastructure. The goal to be achieved in writing the results of this thesis is to find out what types and percentages of damage occurred Abdul Haris Nasution Road Section and maintenance handling and knowing the thickness of the pavement layer required Abdul Haris Nasution Road Section. Road damage is analyzed using the Indonesian Road Capacity Manual Method while flexible pavement thickness planning is adjusted to the Component Analysis Method with a design life of 20 years. From the results of data analysis, it can be concluded that: the types of damage that occur on Jalan Abdul Haris Nasution consist of 2 types, namely: crocodile skin cracks of 10.47% and holes of 6.53%. The percentage value of damage is 17.00%, so the damage category is included in the slight due to the length of the span being reviewed as quite long and the maintenance handling is increasing. The thickness of the pavement layer required on Jalan Abdul Haris Nasution, namely: surface layer 15 cm, upper foundation layer 20 cm and lower foundation layer 10.00 cm.